Leadership Styles in Islamic Boarding Schools and Their Influence on the Quality of Students: A Qualitative Study - Anggun Salsabila Samosir; Firyal Nafilah Az zahra; Shofwatun Niswah; Muhammad Iqbal (Penerbit Hellow Pustaka, 2025)
This qualitative study examines leadership styles in pesantren and their influence on the quality of santri. Conducted at a pesantren in East Java, data were collected through in-depth interviews with leaders, administrators, and santri, participatory observation, and document analysis. Findings reveal that democratic and transformational leadership styles positively affect santri quality, evidenced by enhanced discipline in religious practices, noble character development, and greater independence. In contrast, authoritarian leadership tends to foster passivity among santri. Key challenges include limited managerial competence among leaders and low adaptation to digital technology, which may conflict with traditional pesantren values. The study recommends inclusive leadership practices, improved managerial training for administrators, and the development of innovative curricula rooted in Islamic values. Overall, santri quality can be optimized through flexible, holistic-oriented leadership approaches.